Impact of the Alert Program on School Function for At Risk Cohorts in the Kindergarten Classroom: A Four Year Review of the Data - LaBelle, Leslie (East Carolina University, 2015)
A child’s ability to process, organize, and respond to incoming sensory information and to self-regulate often impacts his or her school performance. The Alert Program, was established with the goal of teaching students the skills needed for self-regulation and therefore, has the potential to yield school function outcomes. This study examined the impact of a classroom approach to the Alert Program on school function for identified at risk students. Retrospective in nature, subjects for this study included 104 kindergarten students at an independent private school in eastern North Carolina between the years 2010-2014. Program implementation consisted of 40-60 minute weekly sessions over 5 months; sessions were led by three to four East Carolina University Occupational Therapy students. Data was collected using the Sensory Processing Measure: Main Classroom (SPM-C) and the School Function Assessment–Part III Activity Performance: Cognitive/Behavioral tasks (SFA). A master panel comprised of early elementary teaching faculty provided input as to what areas of school function are addressed, expected, and most developmentally appropriate at the kindergarten level; feedback revealed that the areas most relevant include: following social conventions, personal care awareness, behavior regulation, task/behavior completion, and positive interaction. Data analysis of student performance on the SFA in each of these pre-identified categories showed significant improvement (p < .05) for identified at risk students after participation in the Alert Program. Results suggest the Alert Program, a sensory-based approach to teaching self-regulation, produces end outcomes in areas of school function, particularly for at risk students. However, while the classroom approach was successful for the majority of students, some students may likely benefit more from an individualized approach.
Keywords: Alert Program; Occupational Therapy; Sensory Integration; School Function Assessment; Sensory Processing Measure; Kindergarten; Response to Intervention; Sensory Processing; Achievement; School